Gastrointestinal Endoscopy in Patients Receiving Antithrombotic Therapy - Supriadi Supriadi; Titong Sugihartono (The Indonesian Society for Digestive Endoscopy, 2021)
Gastrointestinal endoscopy is used as a diagnostic and therapeutic tool. Patients receiving antithrombotic agents are at higher risk for bleeding in this procedure. Regarding its thromboembolic versus bleeding risk, physicians should consider to adjust antithrombotic therapy in patients undergoing gastrointestinal endoscopy. Some important factors including the urgency of the procedure, bleeding risk from the procedure and antithrombotic itself, and the risk of thromboembolic events during endoscopy if antithrombotic is to be stopped need to be considered wisely. Based on recommendations of ASGE, ESGE, and BSG, endoscopic procedures were divided based on the level of emergency, namely elective and urgent. In elective endoscopy with high risk of bleeding and thromboembolism, antithrombotic therapy is given in the minimum duration required and then discontinued before the procedure. In elective endoscopy with low risk of bleeding and thromboembolism, antithrombotic can be continued as usual. In urgent endoscopy due to gastrointestinal bleeding, all antithrombotic should be discontinued. Antithrombotic can be restarted within 48 hours after the procedure if no bleeding is evident